Influence of probiotic on somatic cell count in milk and immune system of dairy cows - Spaniol J.S.* (2015)
© 2014, Springer-Verlag London.The objective of this study is to evaluate the effect of food supplementation with probiotic on milk production and its effect on seric biochemical variables and levels of cytokines in lactating cows. Thirty Holstein cows with production of 32 ± 3.8 kg/day and 129 ± 26 days of lactation were divided randomly into two groups: the control group (without probiotic supplementation) and the treatment group (probiotics from Saccharomyces cerevisiae at a dose of 3 g/day supplied via top dressing). The two groups received the same volume of feed twice a day. Milk volume was measured individually at each milking time. On days 0, 15, 30, and 44, individual milk samples were collected to measure milk composition and somatic cell counts (SCCs). Blood samples were collected on days 0 and 45 to measure urea, total protein, albumin, globulin, and cytokine levels. It was observed that the addition of S. cerevisiae had neither effect on milk production nor on milk composition. On the other hand, animals fed with probiotics showed reduced somatic cell counts on day 15 as well as a tendency in day 30 of study. Urea, total protein, and albumin levels did not differ between groups, but the levels of serum globulins increased on the probiotic-treated group. The treatment group also increased the levels of circulating cytokines [tumor necrosis factor (TNF), interleukin-4 (IL-4), and interferon (IFN)]. The data suggest that the probiotic based on S. cerevisiae when provided to lactating cows is able to enhance their immune system.